Multi-analytical approach to the study of the European glass beads found in the tombs of Kulumbimbi (Mbanza Kongo, Angola) - Costa, Mafalda (2019)
The glass bead assemblages recovered during the 2014 excavations of the ruins of Kulumbimbi located in Mbanza Kongo (Angola) were analyzed by means of a multi-analytical minimally invasive methodology, which includes handheld X-ray fluorescence (hXRF), variable pressure scanning electron microscope coupled with energy dispersive X-ray spectrometry (VP-SEM-EDS), micro-Raman spectroscopy and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Chemical data indicate that cobalt, copper, iron and manganese ions were used to produce the blue, green, reddish-brown and black hues, respectively. Lead arsenates, calcium phosphate, calcium antimonate, lead stannate, cassiterite and Pb-Sb-Sn oxide were used as opacifying agents. Chondrite-normalized trace element distribution and chondrite-normalized rare earth element patterns were used to determine the sand source used in the production of the different glass bead types. These distributions were also used to identify the manufacture location of the glass beads with previously unknown origin and production date. Based on the data collected, the glass beads from types 16, 20, 22, 24, 25, 46 and 47 have been assigned as Venetian.